Screening of Developmental Dysplasia of the Hip in Europe: A Systematic Review - Wojciech Krysta; Patryk Dudek; Łukasz Pulik; Paweł Łęgosz (MDPI AG, 2024)
Background: Developmental dysplasia of the hip (DDH) is a prevalent orthopaedic disorder in children, and screening methods vary across regions due to local health policies. The purpose of this review is to systematise the different ultrasound screening strategies for detecting DDH in newborns in Europe. Methods: Eligible studies from the PubMed, Embase, and Scopus databases, published between 1 January 2018 and 18 March 2023, were included. The inclusion criteria specified a European origin, a focus on newborn human patients, and information on ultrasound for DDH detection. Results: In total, 45 studies were included, covering 18 countries. Among them, six nations (Austria, Bosnia and Herzegovina, Poland, Slovenia, the Czech Republic, and Germany) perform universal ultrasound screening. The timing of the first ultrasound varies, with Austria and the Czech Republic within the 1st week, Bosnia and Herzegovina on the day of birth, Poland between 1 and 12 weeks, and Germany before the 6th week. The Graf method is the most popular ultrasound technique used. Conclusions: There is no consensus on the optimal DDH detection approach in Europe. Varied screening methods stem from epidemiological, cultural, and economic differences among countries.